THE LANGUAGE OF PORTRAITURE IN THE EARLY NINETEENTH-CENTURY NOVEL: A STUDY IN OPIE AND AUSTEN. Issue 1 (2nd January 2016) - Bray, Joe
ABSTRACT: This article examines how two female writers of the early nineteenth century, Amelia Opie and Jane Austen, employ the language of portraiture in their fiction to illustrate the difficulties inherent in the assessment of character, especially for the female heroine. The representation of actual portraits in their work is discussed, along with the use of language associated with the form. Both writers, it is suggested, are aware of important changes within the theory and practice of portraiture in the period, and explore these in their fiction to draw attention to the instability and subjectivity of interpretation.